A crown ether-loaded UiO-66-NH2 mixed matrix membrane and its preparation method and application
By in situ encapsulating crown ether and quaternized poly(biphenyl-piperidine) copolymer in UiO-66-NH2, a crown ether-loaded UiO-66-NH2 mixed matrix membrane was prepared, which solved the problems of low selectivity and complex preparation of polymer membranes and achieved efficient ion separation and selective separation effects.
Patent Information
- Application Number
- CN202510085803.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-09-30
- Estimated Expiration
- 2045-01-20
AI Technical Summary
Existing polymer ion exchange membranes have low selectivity in separating monovalent cations from polyvalent ions, and the chemical reaction grafting method is complex and costly, which limits the improvement of separation efficiency.
Crown ethers were in situ encapsulated into the octahedral cage of UiO-66-NH2 by hydrothermal reaction, and combined with quaternized poly(biphenyl-piperidine) copolymer to prepare crown ether-loaded UiO-66-NH2 mixed matrix membrane, which simplified the preparation process and improved the ion recognition ability.
It achieves highly selective separation of specific ions, significantly reduces the transmembrane transport energy barrier, improves the transport efficiency of monovalent cations, and overcomes the problems of low selectivity and preparation complexity of traditional membranes.
Smart Images

Figure CN119857373B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of mixed matrix membranes, in particular to a crown ether-loaded UiO-66-NH2 mixed matrix membrane and a preparation method and application thereof. Background Art
[0002] Membrane separation technology, due to its high efficiency, energy conservation, and environmental friendliness, has been widely used in water treatment and ion separation, demonstrating unique advantages in the separation of monovalent cations from multivalent ions. The efficient separation of monovalent cations from multivalent ions is crucial for the removal and recovery of heavy metal ions from industrial wastewater, the preparation of battery electrolytes, and the development of salt lake resources. However, the currently widely used polymer ion exchange membranes generally exhibit low selectivity for the separation of monovalent cations from multivalent ions, limiting improvements in separation efficiency.
[0003] Crown ethers are a class of cyclic compounds composed of ether groups (-O-) that can form complexes with a variety of cations, especially metal ions. The naming of crown ethers is based on the size of their rings and the number of oxygen atoms. For example, 15-crown-5 is composed of 15 atoms, 5 of which are oxygen atoms. These oxygen atoms play a key role in binding to cations to form stable complexes. Crown ethers have the property of highly selectively complexing cations and can preferentially bind to specific ions based on the size of the cations. For example, 15-crown-5 prefers to bind to smaller sodium ions (Na + ) complexation.
[0004] Given this characteristic of crown ethers, existing research has sought to overcome the limited selectivity of polymer ion exchange membranes by using crown ethers as functional components and grafting them onto polymer backbones through chemical reactions to improve ion exchange membrane performance. However, this chemical grafting method often suffers from complex reactions and high raw material costs. Summary of the Invention
[0005] In response to the problems existing in the prior art, the present invention provides a crown ether-loaded UiO-66-NH2 mixed matrix membrane, its preparation method, and application. The present invention uses 2,5-diaminoterephthalic acid, a crown ether, and zirconium tetrachloride as raw materials, and obtains the crown ether-loaded UiO-66-NH2 through a hydrothermal reaction. Then, using a quaternized poly(biphenyl-piperidine) copolymer as a base membrane and the crown ether-loaded UiO-66-NH2 as a filler, the quaternized poly(biphenyl-piperidine) copolymer and the crown ether-loaded UiO-66-NH2 are mixed to successfully prepare the crown ether-loaded UiO-66-NH2 mixed matrix membrane. The crown ether-loaded UiO-66-NH2 mixed matrix membrane of the present invention has excellent ion recognition ability, effectively overcoming the low selectivity defect of traditional polymer membranes. At the same time, through in-situ coating technology, the preparation process of the crown ether-loaded UiO-66-NH2 mixed matrix membrane is simplified, overcoming the common shortcomings of the existing chemical reaction grafting method, such as the complex reaction process and high raw material cost.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The first object of the present invention is to provide a method for preparing a crown ether-loaded UiO-66-NH2 mixed matrix membrane, comprising the following steps:
[0008] S1. Add glacial acetic acid to a zirconium tetrachloride solution to obtain solution 1; add crown ether to a 2,5-diaminoterephthalic acid solution to obtain solution 2; mix solution 1 and solution 2 and perform a hydrothermal reaction. During the hydrothermal reaction, 2,5-diaminoterephthalic acid and zirconium tetrachloride undergo coordination polymerization to form a skeleton structure of UiO-66-NH2. At the same time, the crown ether molecules are in situ coated inside the octahedral cage of UiO-66-NH2 to obtain crown ether-loaded UiO-66-NH2; wherein, the reaction of zirconium tetrachloride, 2,5-diaminoterephthalic acid, crown ether and glacial acetic acid is carried out. The molar ratio is 0.5-2:0.5-2:1.77:100; UiO-66-NH2 crystals loaded with crown ether can be obtained without affecting the crystal structure of UiO-66-NH2; 2,5-diaminoterephthalic acid can provide positive charges and hinder the transport of cations, especially multivalent cations; directly mixing zirconium tetrachloride, glacial acetic acid, 2,5-diaminoterephthalic acid and crown ether will interfere with the interaction between the four substances, resulting in a decrease in the quality of UiO-66-NH2 loaded with crown ether, or even the failure to obtain UiO-66-NH2 loaded with crown ether.
[0009] S2, after dispersing the positively charged polymer and the crown ether-loaded UiO-66-NH2 in an organic solvent, mixing them to obtain a casting solution; in the casting solution, the crown ether-loaded UiO-66-NH2 accounts for 5% to 20% of the casting solution mass; the content of the crown ether-loaded UiO-66-NH2 is about 1% to 20% of the Na+ , K + The transport of ions has a significant promoting effect. When ions are transported to the surface of the UiO-66-NH2 mixed matrix membrane loaded with crown ether, they will be repelled by the positive charge on the surface of the UiO-66-NH2 mixed matrix membrane loaded with crown ether and the energy barrier generated by its own dehydration. At this time, these factors jointly hinder the transport behavior of ions. However, 15-crown ether-5 and Na + The strong complexation can capture Na + , thereby reducing its dehydration energy barrier and effectively compensating for the hydrated Na + The increased energy barrier due to the removal of water molecules from the hydration layer reduces the Na + The energy barrier of the entire crown ether-loaded UiO-66-NH2 mixed matrix membrane promotes the Na + transmission.
[0010] In addition, the quaternized poly(biphenyl-piperidine) copolymer is positively charged, which helps to inhibit the transport of multivalent cations.
[0011] S3. The casting solution is made into a liquid film, and after evaporating the solvent, a crown ether-loaded UiO-66-NH2 mixed matrix membrane is obtained.
[0012] Preferably, the molar ratio of zirconium tetrachloride, 2,5-diaminoterephthalic acid, crown ether and glacial acetic acid is 1:1:1.77:100.
[0013] Preferably, the hydrothermal reaction conditions are: reaction at 80° C. to 150° C. for 12 h to 72 h.
[0014] Preferably, the crown ether is selected from 15-crown-5 or 18-crown-6; when the crown ether is 15-crown-5, the prepared crown ether-loaded UiO-66-NH2 mixed matrix membrane has sodium ion transport ability and is a high Na + / Mg 2+ Selective separation membrane; when the crown ether is 18-crown-6, the prepared crown ether-loaded UiO-66-NH2 mixed matrix membrane has potassium ion transport ability and is a high K + / Mg 2+ Selective separation membrane.
[0015] Preferably, after the hydrothermal reaction is completed, the crown ether-loaded UiO-66-NH2 is washed, dried, and ground; the grinding time cannot be longer than 15 minutes, as too long will cause the crown ether-loaded UiO-66-NH2 particles to aggregate in flaky form, making it difficult to disperse in an organic solvent.
[0016] Preferably, the positively charged polymer is selected from quaternized polybiphenyl-piperidine copolymer or quaternized polyterphenyl-piperidine copolymer.
[0017] Preferably, the solvents of the zirconium tetrachloride solution and the 2,5-diaminoterephthalic acid solution are both N,N'-dimethylformamide.
[0018] The second object of the present invention is to provide a crown ether-loaded UiO-66-NH2 mixed matrix membrane prepared by the above preparation method.
[0019] The third object of the present invention is to provide the use of the above-mentioned crown ether-loaded UiO-66-NH2 mixed matrix membrane in the preparation of ion separation membranes.
[0020] The fourth object of the present invention is to provide the use of the above-mentioned crown ether-loaded UiO-66-NH2 mixed matrix membrane in the preparation of water purification membranes.
[0021] A fifth object of the present invention is to provide the use of the above-mentioned crown ether-loaded UiO-66-NH2 mixed matrix membrane in the preparation of value-added ion enrichment membranes.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention provides a method for preparing a crown ether-loaded UiO-66-NH2 mixed matrix membrane, comprising the steps of adding glacial acetic acid to a zirconium tetrachloride solution to obtain a first solution; adding a crown ether to a 2,5-diaminoterephthalic acid solution to obtain a second solution; mixing the first solution with the second solution and subjecting the mixture to a hydrothermal reaction, wherein during the hydrothermal reaction, 2,5-diaminoterephthalic acid coordinates with zirconium tetrachloride to form a UiO-66-NH2 skeleton structure, and simultaneously, the crown ether molecules are in situ coated inside the octahedral cage of the UiO-66-NH2 to obtain a crown ether-loaded UiO-66-NH2; wherein zirconium tetrachloride, 2,5-diaminoterephthalic acid, The molar ratio of terephthalic acid, crown ether, and glacial acetic acid is 0.5-2:0.5-2:1.77:100; the quaternized poly(biphenyl-piperidine) copolymer and the crown ether-loaded UiO-66-NH2 are dispersed in an organic solvent respectively and then mixed. The dispersion in the organic solvent and then mixing helps to improve the compatibility of the crown ether-loaded UiO-66-NH2 and the quaternized poly(biphenyl-piperidine) copolymer, thereby obtaining a casting solution; in the casting solution, the crown ether-loaded UiO-66-NH2 accounts for 5% to 20% of the mass of the casting solution; the casting solution is made into a liquid membrane to obtain a crown ether-loaded UiO-66-NH2 mixed matrix membrane. The crown ether-loaded UiO-66-NH2 mixed matrix membrane of the present invention has good ion recognition ability and effectively overcomes the defect of low selectivity of traditional polymer membranes. At the same time, the in-situ coating technique simplifies the preparation process of the crown ether-loaded UiO-66-NH2 mixed matrix membrane, overcoming the complex reaction process and high raw material costs commonly encountered in existing chemical reaction grafting methods. Furthermore, the introduction of the crown ether imparts the crown ether-loaded UiO-66-NH2 mixed matrix membrane with high selectivity for specific ions. The crown ether-loaded UiO-66-NH2, or MOF structure, provides excellent pore control capabilities, enhancing the membrane's separation performance.
[0024] 2. The crown ether-loaded UiO-66-NH2 mixed matrix membrane provided by the present invention significantly reduces the Na2+ interaction with the crown ether due to its in-situ loaded crown ether structure. + , K + ions (specifically, 15-crown-5 and Na + Has strong complexation with K + It shows a weak complexation; while 18-crown-6 and K +The transmembrane transport energy barrier (which exhibits a strong complexation effect) effectively promotes the transport efficiency of these ions, thereby achieving selectivity far exceeding that of ordinary mixed-matrix membranes. Furthermore, the positively charged UiO-66-NH2 component synergizes with the polymer matrix to form a transport barrier for like-charged cations, especially multivalent ions with higher charge states, effectively inhibiting the transport of these ions through the polymer and further ensuring that the crown ether-loaded UiO-66-NH2 mixed-matrix membrane can exhibit excellent selectivity for monovalent cations and multivalent ions. This excellent performance is achieved thanks to the dual combination mechanism of the crown ether's specific recognition function and electrostatic effect.
[0025] 3. By combining the specific recognition ability of crown ethers with the electrostatic effect, the crown ether-loaded UiO-66-NH2 mixed matrix membrane prepared by the present invention can be used to prepare ion separation, water purification or high-value-added ion enrichment membranes, showing good application potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 These are the nuclear magnetic resonance images of the crown ether-loaded UiO-66-NH2 mixed matrix membranes prepared in Example 1 and Example 6, where (a) is Example 1 and (b) is Example 6.
[0027] Figure 2 XRD patterns of the crown ether-loaded UiO-66-NH2 mixed matrix membranes prepared in Examples 1 and 6 and the UiO-66-NH2 prepared in Comparative Example 2.
[0028] Figure 3 These are nitrogen adsorption and desorption curves of 15C5@UiO-66 prepared in Example 1 and UiO-66 prepared in Comparative Example 2, where (a) is Example 1 and (b) is Comparative Example 2.
[0029] Figure 4 These are the XRD patterns of the crown ether-loaded UiO-66-NH2 mixed matrix membranes prepared in Examples 1 to 5 and the quaternized poly(biphenyl-piperidine) copolymer membrane prepared in Comparative Example 1.
[0030] Figure 5 This is a diagram of the electrodialysis device used in the present invention.
[0031] Figure 6 These are the results of the two-component electrodialysis separation performance of the crown ether-loaded UiO-66-NH2 mixed matrix membranes prepared in Examples 1 to 5 of the present invention and the quaternized poly(biphenyl-piperidine) copolymer membrane prepared in Comparative Example 1, wherein (a) is Comparative Example 1, (b) is Example 1, (c) is Example 2, (d) is Example 3, (e) is Example 4, and (f) is Example 5.
[0032] Figure 7 The temperature-flux relationship diagram and transmembrane energy barrier numerical diagram during ion migration of the crown ether-loaded UiO-66-NH2 mixed matrix membrane prepared in Example 3 of the present invention, wherein (a) is the temperature-flux relationship diagram, and (b) is the transmembrane energy barrier numerical diagram. DETAILED DESCRIPTION
[0033] The following will be combined with the data in the examples of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Among them, 15-crown-5 and 18-crown-6 were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., AR grade.
[0034] Although membrane separation technology has shown broad application prospects in the field of ion separation, the selectivity limitations and complexity of traditional polymer ion exchange membranes remain key factors restricting their performance improvement. Crown ethers, as compounds with highly selective binding properties, have potential application value in the field of ion separation. Currently, in applications in the field of ion separation, crown ethers are mainly grafted onto polymer backbones through chemical reactions or used to synthesize porous crystalline materials containing crown ethers. However, chemical reaction grafting methods generally have the disadvantages of complex reactions and high raw material costs.
[0035] In view of the defects of the above-mentioned prior art, the present invention provides a method for preparing a UiO-66-NH2 mixed matrix membrane loaded with a crown ether, comprising the following steps: adding glacial acetic acid to a zirconium tetrachloride solution to obtain a first solution; adding a crown ether to a 2,5-diaminoterephthalic acid solution to obtain a second solution; mixing the first solution and the second solution and performing a hydrothermal reaction, wherein during the hydrothermal reaction, the 2,5-diaminoterephthalic acid and the zirconium tetrachloride undergo coordination polymerization to form a UiO-66-NH2 skeleton structure, and at the same time, the crown ether molecules are in situ coated onto the UiO-66-NH2. Inside the octahedral cage, crown ether-loaded UiO-66-NH2 is obtained; wherein, the molar ratio of zirconium tetrachloride, 2,5-diaminoterephthalic acid, crown ether and glacial acetic acid is 0.5-2:0.5-2:1.77:100; the quaternized polybiphenyl-piperidine copolymer and the crown ether-loaded UiO-66-NH2 are dispersed in an organic solvent respectively, and then mixed to obtain a casting solution; in the casting solution, the crown ether-loaded UiO-66-NH2 accounts for 5% to 20% of the mass of the casting solution; the casting solution is prepared into a liquid membrane to obtain a crown ether-loaded UiO-66-NH2 mixed matrix membrane.
[0036] The crown ether-loaded UiO-66-NH2 mixed matrix membrane of the present invention has good ion recognition ability, effectively overcoming the defect of low selectivity of traditional polymer membranes. At the same time, through in-situ coating technology, the preparation process of the crown ether-loaded UiO-66-NH2 mixed matrix membrane is simplified, overcoming the common shortcomings of the existing chemical reaction grafting method such as complex reaction process and high raw material cost.
[0037] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.
[0038] Example 1
[0039] A method for preparing a crown ether-loaded UiO-66-NH2 mixed matrix membrane comprises the following steps:
[0040] S1. Dissolve 191 mg of zirconium tetrachloride in 41 mL of N,N'-dimethylformamide, and add 4.83 g of glacial acetic acid for later use; at the same time, dissolve 146 mg of 2,5-diaminoterephthalic acid in 41 mL of N,N'-dimethylformamide, and add 400 μL of 15-crown ether-5 for later use; mix the two solutions and perform ultrasonic treatment for 10 minutes, then stir for 1 hour, cycle ultrasonication and stirring three times, and then transfer to a hydrothermal reactor for hydrothermal reaction at 120°C for 48 hours. After the reaction is completed, wash the product three times with N,N'-dimethylformamide and methanol, respectively. After washing, dry the product in a vacuum drying oven at 60°C; after drying, grind it in a mortar for 15 minutes to obtain crown ether-loaded UiO-66-NH2, which is recorded as 15C5@UiO-66-NH2, also recorded as 15C5@UiO-66.
[0041] S2. Dissolve 1.54 g, 10 mmol, of biphenyl and 1.343 mL, 12 mmol, of N-methyl-4-piperidone in 8.8 mL of dichloromethane. Add 740 μL, 10 mmol, of trifluoroacetic acid and 8.8 mL, 100 mmol, of trifluoromethanesulfonic acid dropwise in an ice bath. Stir the mixture for 5 h in an ice bath until a viscous deep red solution is obtained and the reaction is complete. Subsequently, the product is slowly poured into an aqueous solution to obtain a white fibrous substance, which is thoroughly washed with deionized water until the mixture is completely eluted. The reaction mixture was neutralized and then dried to obtain a poly(biphenylpiperidine) copolymer, namely PBPIP; 1.0 g of PBPIP was dissolved in 20 mL of dimethyl sulfoxide, and 320 μL (1.3 eq.) of iodomethane solution was added; the reaction was carried out at room temperature under light-proof conditions for 16 h to obtain an orange-red solution; the solution was poured into ethyl acetate to obtain a yellow fibrous solid, which was washed with deionized water, filtered, and dried in a vacuum drying oven at 60°C to obtain a quaternized poly(biphenyl-piperidine) copolymer, denoted as QPBPIP.
[0042] S3. At room temperature, 0.0053 g of 15C5@UiO-66-NH2 was dispersed in 1 mL of dimethyl sulfoxide and subjected to ultrasonic dispersion treatment. At the same time, 0.1 g of QPBPip was dissolved in 1 mL of dimethyl sulfoxide and fully dissolved by oscillation. The two solutions were then mixed evenly and ultrasonically treated again for 30 s to obtain a casting solution.
[0043] S4. The casting solution was evenly coated on a glass plate to form a membrane area of 4 cm × 4 cm. The membrane was then placed on a hot plate at 70°C to evaporate the solvent by heating. After the membrane was completely solidified, the membrane was removed from the glass plate to obtain a crown ether-loaded UiO-66-NH2 mixed matrix membrane, i.e., 15C5@UiO / QPBPip, recorded as 5 wt%.
[0044] Example 2
[0045] A method for preparing a crown ether-loaded UiO-66-NH2 mixed matrix membrane is the same as the preparation method in Example 1, except that the mass of 15C5@UiO-66-NH2 in S3 is replaced from 0.0053 g to 0.0111 g, obtaining a crown ether-loaded UiO-66-NH2 mixed matrix membrane, i.e., 15C5@UiO / QPBPip, recorded as 10 wt%.
[0046] Example 3
[0047] A method for preparing a crown ether-loaded UiO-66-NH2 mixed matrix membrane is the same as the preparation method in Example 1, except that the mass of 15C5@UiO-66-NH2 in S2 is replaced from 0.0053 g to 0.0176 g, obtaining a crown ether-loaded UiO-66-NH2 mixed matrix membrane, i.e., 15C5@UiO / QPBPip, recorded as 15 wt%.
[0048] Example 4
[0049] A method for preparing a crown ether-loaded UiO-66-NH2 mixed matrix membrane is the same as the preparation method in Example 1, except that the mass of 15C5@UiO-66-NH2 in S3 is replaced from 0.0053 g to 0.0212 g, obtaining a crown ether-loaded UiO-66-NH2 mixed matrix membrane, i.e., 15C5@UiO / QPBPip, recorded as 17.5 wt%.
[0050] Example 5
[0051] A method for preparing a crown ether-loaded UiO-66-NH2 mixed matrix membrane is the same as the preparation method in Example 1, except that the mass of 15C5@UiO-66-NH2 in S3 is replaced from 0.0053 g to 0.0250 g, obtaining a crown ether-loaded UiO-66-NH2 mixed matrix membrane, i.e., 15C5@UiO / QPBPip, recorded as 20 wt%.
[0052] Example 6
[0053] A method for preparing a crown ether-loaded UiO-66-NH2 mixed matrix membrane is the same as the preparation method of Example 1, except that 15-crown-5 in S1 is replaced by 18-crown-6, comprising the following steps:
[0054] S1. Dissolve 191 mg of zirconium tetrachloride in 41 mL of N,N'-dimethylformamide, and add 4.83 g of glacial acetic acid for later use; at the same time, dissolve 146 mg of 2,5-diaminoterephthalic acid in 41 mL of N,N'-dimethylformamide, and add 400 μL of 18-crown-6 for later use; mix the two solutions and perform ultrasonic treatment for 10 minutes, then stir for 1 hour, cycle ultrasonication and stirring three times, and then transfer to a hydrothermal reactor for hydrothermal reaction at 120°C for 48 hours. After the reaction is completed, wash the product three times with N,N'-dimethylformamide and methanol, respectively. After washing, dry the product in a vacuum drying oven at 60°C; after drying, grind it in a mortar for 15 minutes to obtain crown ether-loaded UiO-66-NH2, recorded as 18C6@UiO-66-NH2.
[0055] S2. At room temperature, 0.0053 g of 18C6@UiO-66-NH2 was dispersed in 1 mL of dimethyl sulfoxide and subjected to ultrasonic dispersion treatment. At the same time, 0.1 g of QPBPip was dissolved in 1 mL of dimethyl sulfoxide and fully dissolved by oscillation. The two solutions were then mixed evenly and ultrasonically treated again for 30 s to obtain a casting solution.
[0056] S3. The casting solution was evenly coated on a glass plate to form a 4 cm × 4 cm membrane area. The membrane was then placed on a hot plate at 70°C to evaporate the solvent by heating. After the membrane was completely solidified, it was removed from the glass plate to obtain a crown ether-loaded UiO-66-NH2 mixed matrix membrane, denoted as 18C6@UiO / QPBPip.
[0057] Example 7
[0058] A method for preparing a crown ether-loaded UiO-66-NH2 mixed matrix membrane is the same as the preparation method in Example 1, except that the material amounts in S1 are replaced by 95.5 mg of zirconium tetrachloride, 73 mg of 2,5-diaminoterephthalic acid, and 452 μL of 15-crown ether-5 instead of 191 mg of zirconium tetrachloride, 146 mg of 2,5-diaminoterephthalic acid, and 400 μL of 15-crown ether-5 to obtain a crown ether-loaded UiO-66-NH2 mixed matrix membrane.
[0059] Example 8
[0060] A method for preparing a crown ether-loaded UiO-66-NH2 mixed matrix membrane is the same as the preparation method in Example 1, except that the material amounts in S1 are replaced by 382 mg of zirconium tetrachloride and 292 mg of 2,5-diaminoterephthalic acid instead of 191 mg of zirconium tetrachloride and 146 mg of 2,5-diaminoterephthalic acid to obtain a crown ether-loaded UiO-66-NH2 mixed matrix membrane.
[0061] Comparative Example 1
[0062] A method for preparing a QPBPip membrane comprises the following steps:
[0063] S1. Dissolve 1.54 g, 10 mmol, of biphenyl and 1.343 mL, 12 mmol, of N-methyl-4-piperidone in 8.8 mL of dichloromethane. Add 740 μL, 10 mmol, of trifluoroacetic acid and 8.8 mL, 100 mmol, of trifluoromethanesulfonic acid dropwise in an ice bath. Stir the mixture in an ice bath for 5 h until a viscous deep red solution is obtained, and the reaction is complete. Subsequently, slowly pour the product into an aqueous solution to obtain a white fibrous substance. The substance is thoroughly washed with deionized water until neutral, and then dried to obtain a poly(biphenylpiperidine) copolymer, designated as PBPIP.
[0064] S2. Dissolve 1.0 g of PBPIP in 20 mL of dimethyl sulfoxide, add 320 μL (1.3 eq.) of iodomethane solution; react at room temperature under light-shielding conditions for 16 h to obtain an orange-red solution; pour the solution into ethyl acetate to obtain a yellow fibrous solid, wash with deionized water, filter, and dry in a vacuum drying oven at 60° C. to obtain a quaternized polybiphenyl-piperidine copolymer, recorded as QPBPIP.
[0065] S3. At room temperature, 0.1 g of QPBPIP was dissolved in 2 mL of dimethyl sulfoxide and fully dispersed by ultrasonic dispersion. Subsequently, a 4 cm × 4 cm area was coated on a glass plate. The glass plate was placed on a hot plate at 70°C. After the solvent was completely evaporated, the film was removed to obtain a quaternized polybiphenyl-piperidine copolymer film, which was recorded as QPBPip film and recorded as 0 wt%.
[0066] Comparative Example 2
[0067] A method for preparing UiO-66-NH2 is the same as the method in Example 1, except that 15-crown-5 is not added in S1, and comprises the following steps:
[0068] 191 mg of zirconium tetrachloride was dissolved in 41 mL of N,N'-dimethylformamide, and 4.83 g of glacial acetic acid was added for later use; at the same time, 146 mg of 2,5-diaminoterephthalic acid was dissolved in 41 mL of N,N'-dimethylformamide for later use; the two solutions were mixed and ultrasonically treated for 10 minutes, then stirred for 1 hour, and transferred to a hydrothermal reactor after three cycles of ultrasonication and stirring, and reacted at 120°C for 48 hours. After the reaction was completed, the product was washed three times with N,N'-dimethylformamide and methanol, respectively. After washing, the product was placed in a vacuum drying oven at 60°C for drying; after drying, it was ground in a mortar for 15 minutes to obtain UiO-66-NH2, recorded as UiO-66.
[0069] Characterization and monovalent and divalent ion separation performance testing:
[0070] (1) Characterization
[0071] In order to verify the existence of crown ether in UiO-66-NH2 loaded with crown ether, the structure was destroyed by NaOH treatment to release the encapsulated crown ether molecules. Subsequently, the released products were analyzed by nuclear magnetic resonance technology to observe Figure 1 It was found that characteristic peaks of -CH2-CH2- groups in 15-crown-5 and 18-crown-6 were observed at chemical shifts of 3.38 ppm and 3.61 ppm, respectively, proving that the crown ether molecules had been successfully encapsulated inside the framework of UiO-66-NH2.
[0072] observe Figure 2 The results show that the diffraction peak positions of UiO-66-NH2, 15C5@UiO-66-NH2, and 18C6@UiO-66-NH2 are consistent and have similar intensities. This result shows that the introduction of crown ether has no significant effect on the crystal structure of UiO-66-NH2, and 15C5@UiO-66-NH2 and 18C6@UiO-66-NH2 still maintain good crystallinity.
[0073] observe Figure 3 It was found that when UiO-66-NH2 was loaded with 15-crown ether-5, the crown ether molecules occupied part of the space inside the UiO-66-NH2 cavity, which increased the specific surface area of UiO-66-NH2 from 813.9618 m 2 / g dropped to 723.2601m 2 / g, further proving that 15-crown ether-5 has been successfully encapsulated into the UiO-66-NH2 structure.
[0074] observe Figure 4 Compared to the QPBPip membrane prepared in Comparative Example 1, the 15C5@UiO-66-NH2 prepared in Examples 1 to 5 exhibited significant diffraction peaks at approximately 7.4° and 8.5° attributable to UiO-66-NH2, demonstrating that UiO-66-NH2 maintains its structural integrity within the 15C5@UiO / QPBPip membrane. A faint diffraction peak was observed at approximately 25.5°. Due to the QPBPip encapsulation effect, it was almost absent when the 15C5@UiO-66-NH2 content was below 15wt%. However, it became increasingly prominent with increasing 15C5@UiO-66-NH2 content, further demonstrating the structural integrity and good crystallinity of 15C5@UiO-66-NH2 within the 15C5@UiO / QPBPip membrane, providing structural support for subsequent ion separation.
[0075] (2) Monovalent and divalent ion separation performance test
[0076] The 15C5@UiO / QPBPip membranes prepared in Examples 1 to 5 and the QPBPip membrane prepared in Comparative Example 1 were used as the monovalent cation and multivalent cation selective separation membranes to construct an electrodialysis device. The membrane stack structure is as follows: Figure 5 As shown, it includes a positive electrode plate, a commercial anion exchange membrane, a polymer-based covalent organic framework membrane, a commercial anion exchange membrane, and a negative electrode plate. The membrane stack forms four compartments: an anode compartment, a desalination compartment, a concentration compartment, and a cathode compartment. The effective area of the membrane in this device that allows ions to pass through is 2.00 cm 2 The electrodialysis experiment was run in constant current mode with a temperature of 25°C and a current density of 2 mA·cm -2 , the test time is 1h.
[0077] Electrodialysis testing is divided into single-component ion system and two-component mixed ion system, as follows:
[0078] Single-component ion system: the electrode chamber is 100mL, 0.3mol / L Na2SO4 solution, the desalination chamber is 100mL, 0.1mol / L MCl X (M=K, Na, Li or Mg) solution, the concentrating chamber is 100mL deionized water.
[0079] Two-component mixed ion system: the electrode chamber is 100 mL of 0.3 mol / L Na2SO4 solution, the desalination chamber is 100 mL of a mixed solution of 0.1 mol / L MCl (M = K, Na or Li) and 0.1 mol / L MgCl2, and the concentration chamber is 100 mL of deionized water.
[0080] After the test is completed, the solution in the concentration chamber is collected and the cation concentration to be measured is detected by inductively coupled plasma emission spectroscopy. The cation flux calculation formula is as follows:
[0081]
[0082] Among them, J (mol·m -2 ·h -1 ) represents the cation flux, C t (moL·L -1 ) and C0(moL·L -1 ) are the concentrations of ions in the concentration chamber at time t and time 0, V(L) is the liquid volume in the concentration chamber, t(h) is the test time, and A m (m 2 ) is the effective area of the membrane during the test.
[0083] The selectivity between monovalent cations and polyvalent cations can be calculated using the following formula:
[0084]
[0085] in: is a cation M + and M 2+ The selectivity, and To desalinate indoor cation M + and M 2+ concentration.
[0086] observe Figure 6 Figures (b), (c), (d), (e) and (f) show that on the same 15C5@UiO / QPBPip membrane, the order of ion selectivity is S Na+ / Mg2+ >S K+ / Mg2+ >S Li+ / Mg2+ This is mainly attributed to the difference in diameter of different ions and their coordination ability with 15-crown-5. Specifically, Li + The diameter is Na + The diameter is K + The diameter is The cavity size of 15-crown-5 is between Therefore, Na + The diameter of K is more compatible with the cavity size of 15-crown-5, and its coordination ability is stronger. + The diameter is slightly larger than the cavity size, but can still pass through the "crown ether-K + -crown ether" hamburger-like structure forms a weak coordination with 15-crown ether-5. In contrast, Li + The diameter of 15-crown-5 is smaller than that of the crown ether cavity, making it difficult to effectively match the 15-crown-5 cavity and achieve coordination complexation. Therefore, the order of the strength of the interaction between 15-crown-5 and these three ions through recognition and coordination complexation is Na + >K + >>Li + When these three ions are transported across the positively charged 15C5@UiO / QPBPip membrane, their transport is hindered due to the mutual repulsion of like charges. However, the presence of the crown ether effectively compensates for the energy required for ion transport, lowering the transport energy barrier for the corresponding ions. As a result, ions with a higher degree of compatibility with the crown ether can pass through the membrane more quickly, achieving selective transport.
[0087] In addition, as the 15C5@UiO-66-NH2 content increases from 0wt% to 5wt%, 10wt% and even 15wt%, the selectivity of different ions shows a trend of significantly increasing with the increase of 15C5@UiO-66-NH2 content, among which S Na+ / Mg2+The selectivity increase is the most obvious. This is mainly due to the crown ether's ability to recognize and strongly complex Na + , Na + The energy barrier through the membrane is significantly reduced. Compared with other multivalent ions, Na + Able to pass through the mixed matrix membrane quickly, thus obtaining Na + / Mg 2+ Selectivity. With the increase of 15C5@UiO-66-NH2 content, the crown ether content increases, and this promoting effect is further enhanced. + / Mg 2+ Selectivity also increases.
[0088] like Figure 6 In Figures (d), (e) and (f), as the content of 15C5@UiO-66-NH2 increases from 15wt% to 17.5wt% and even 20wt%, the selectivity of each ion decreases with the increase of 15C5@UiO-66-NH2 content. 2+ With a higher charge state and a larger hydrated ion size, it is relatively difficult for it to pass through the 15C5@UiO / QPBPip membrane. However, with the increase of 15C5@UiO-66-NH2 content, the agglomeration of 15C5@UiO-66-NH2 becomes more and more obvious. The agglomeration of 15C5@UiO-66-NH2 in local areas deteriorates the compatibility between 15C5@UiO-66-NH2 and QPBPip, thereby forming a large number of vacancies at the "filler-QPBPip" interface. These vacancies are Mg 2+ At the same time, the agglomeration of 15C5@UiO-66-NH2 also caused the local area 15C5@UiO-66-NH2 to be much higher than the overall level. At this time, the irregular arrangement of 15C5@UiO-66-NH2 resulted in a large number of gaps between the "filler particles-filler particles", which provided a potential permeation channel for Mg. 2+ It provides a new, almost unimpeded transmission path for the transmission of
[0089] The combined effect of the above two factors resulted in a significant decrease in the selectivity of each ion with the continuous increase of the 15C5@UiO-66-NH2 content.
[0090] Depend on Figure 7 Based on the temperature-flux relationship in (a), the energy barriers for different ions to cross the membrane in the 15C5@UiO / QPBPip membrane with a filler content of 15% were calculated. Figure 7 As shown in (b), the order of the transmembrane transport energy barrier is: Mg 2+ >Na + >K + >Li+ Since the 15C5@UiO / QPBPip membrane itself carries a positive charge, magnesium ions are subject to a greater electrostatic repulsion than monovalent ions, resulting in a higher energy barrier for transmembrane transport. At the same time, the hydration radius and ion size of magnesium ions are also larger, so the transmembrane energy barrier of magnesium ions is the highest. As mentioned above, Na + The complexation with 15-crown ether-5 promoted the entry of sodium ions into the 15C5@UiO / QPBPip membrane, compensating for the energy barrier increase caused by the positive charge of the basement membrane itself, and reducing the Na + The transmembrane energy barrier across the entire 15C5@UiO / QPBPip membrane.
[0091] It should be noted that when the present invention involves numerical ranges, it should be understood that both endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes preferred embodiments. Although preferred embodiments of the present invention have been described, those skilled in the art will be able to make additional changes and modifications to these embodiments once they understand the basic inventive concepts. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0092] It is obvious that those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if such changes and modifications of the present invention fall within the scope of the claims and their equivalents, the present invention is intended to include such changes and modifications.
Claims
1. A method for preparing a crown ether-loaded UiO-66-NH2 mixed matrix membrane, characterized in that: The following steps are involved: Add glacial acetic acid to the zirconium tetrachloride solution to obtain solution 1; adding crown ether to the 2,5-diaminoterephthalic acid solution to obtain solution 2; Solution 1 and solution 2 were mixed and subjected to a hydrothermal reaction. During the hydrothermal reaction, 2,5-diaminoterephthalic acid and zirconium tetrachloride underwent coordination polymerization to form the skeleton structure of UiO-66-NH2. At the same time, the crown ether molecules were in situ encapsulated inside the octahedral cage of UiO-66-NH2 to obtain crown ether-loaded UiO-66-NH2. The molar ratio of zirconium tetrachloride, 2,5-diaminoterephthalic acid, crown ether and glacial acetic acid is 0.5-2:0.5-2:1.77-2:100; The positively charged polymer and the crown ether-loaded UiO-66-NH2 are dispersed in an organic solvent and then mixed to obtain a casting solution; In the casting solution, the crown ether-loaded UiO-66-NH2 accounts for 5% to 20% of the casting solution mass; The casting solution was made into a liquid membrane to obtain a crown ether-loaded UiO-66-NH2 mixed matrix membrane.
2. The method for preparing a crown ether-loaded UiO-66-NH2 mixed matrix membrane according to claim 1, wherein: The molar ratio of zirconium tetrachloride, 2,5-diaminoterephthalic acid, crown ether and glacial acetic acid is 1:1:1.77:
100.
3. The method for preparing a crown ether-loaded UiO-66-NH2 mixed matrix membrane according to claim 1, wherein The conditions of the hydrothermal reaction are: reaction at 80°C to 150°C for 12h to 72h.
4. The method for preparing a crown ether-loaded UiO-66-NH2 mixed matrix membrane according to claim 1, wherein: The crown ether is selected from 15-crown-5 or 18-crown-6.
5. The method for preparing a crown ether-loaded UiO-66-NH2 mixed matrix membrane according to claim 1, wherein: The positively charged polymer is selected from quaternized polybiphenyl-piperidine copolymers or quaternized polyterphenyl-piperidine copolymers.
6. The method for preparing a crown ether-loaded UiO-66-NH2 mixed matrix membrane according to claim 1, wherein: The solvents of the zirconium tetrachloride solution and the 2,5-diaminoterephthalic acid solution are both N,N'-dimethylformamide.
7. A crown ether-loaded UiO-66-NH2 mixed matrix membrane prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the crown ether-loaded UiO-66-NH2 mixed matrix membrane according to claim 7 in the preparation of an ion separation membrane.
9. Use of the crown ether-loaded UiO-66-NH2 mixed matrix membrane according to claim 7 in the preparation of a water purification membrane.
10. Use of the crown ether-loaded UiO-66-NH2 mixed matrix membrane according to claim 7 in the preparation of value-added ion enrichment membranes.
